Sustainable Finance for Off-Grid Solar Irrigation: IPSR Innovation Profile - Dahl, Hauke; Magombeyi, Manuel Simba (2022)
Addressing physical and economic water scarcity through the provision of off-grid solar pumps to smallholder farmers in key-value chains and supporting adaption through sustainable finance solutions in Zambia. In many off-grid areas, petrol and diesel pumps are commonly used for irrigation. However, they are expensive to run and contribute to environmental pollution. With the abundance of sunshine in Sub Sahara Africa, solar pumps offer small farmers a promising alternative – if they can afford the initial investment. Financial mechanisms like pay-as-you-go models are linked to asset sales to decrease the investment threshhold for smallhold farmers.